Association between Adiposity Indices and Blood Pressure among Young Adults: A Cross Sectional Study - Jha, Reena Kumari; Risal, Prabod; Shah, Sakshi; Singh, Chiranjeet Kumar; Mishra, Abadhesh Kumar; Nepal, Ojashwi (Journal of Nobel Medical College, 2025)
Background: The prevalence of obesity is rising rapidly in many low and middle income countries and is strongly linked to an increased risk of cardiovascular disease (CVD) and related health complications. Thus, this study aimed to see the association between adiposity indices and blood pressure using different markers of obesity among young adults.Materials and Methods: A cross sectional study was carried out in the Kathmandu University School of Medical Sciences, from June to August 2025. A total of 426 participants, aged 18 – 30 years were enrolled through convenience sampling. The height in meter, weight in Kg, hip circumference and waist circumference in centimeter were recorded for each participant than body adiposity index, body mass index, waist hip ratio and waist height ratio were calculated. Blood pressure was recorded by digital sphygmomanometer. Gender comparison was made and independent sample t-test, ANOVA and Pearson’s correlation analysis was used.Results: Out of total 426 participants, 174 were males and 252 were females.  24.71% males and 12.30% females were overweight/obese. Body adiposity index, hip circumference, waist circumference, waist to height ratio and waist to hip ratio were higher in males compared to females. Considering BMI, systolic and diastolic blood pressure tends to increase in overweight/obese participants but insignificant. Mean BAI was 22.00±6.14, whilst 29.17% had a body fat percentage in the overweight/obese category. Considering BAI, overweight/obese female had higher systolic and diastolic blood pressure.Conclusion: Our findings concludes that overweight/obese females are more prone to develop hypertension in future.